Morfometria dos músculos sóleo e gastrocnêmio após imobilização na posição encurtada do membro pélvico de ratos, durante 15, 30 e 45 dias - Ana Paula Guimaraes de Sousa (2011)
Thirty young male Wistar rats were subjected to immobilization for the study of hind limb skeletal muscle atrophy. Animals were split into six groups (6 rats per treated group: I, for 15 days; II, 30 days; III, 45 days, and 4 mice / control group: IV, 15 days, V, VI and 30 days, 45 days). After such intervals, the gastrocnemius and soleus muscles were dissected and weighed. The muscle bellies were sectioned for histological, immunohistochemical and morphometric analysis, and cryotomized for myofibrillar ATPases determination. The body weights and gastrocnemius and soleus muscles were compiled. Stained histological sections (hematoxylin eosin, PicroSiriusRed,) and sections histochemistry (ATPase) were analyzed morphometrically (number of cells and nuclei, cell sizes, connective muscle area, muscle fiber types). Nerve fibers (sections histological - Glees-Marsland) and the nuclei in apoptosis and/or nuclear autophagocytosis (sections Immunohistochemistry - Caspase 3) were analyzed qualitatively. Immobilization caused skeletal muscle atrophy and a significant reduction in body and muscular weight. The number of cells and nuclei increased as well as the average area of connective tissue. The muscular dimensions (area, perimeter and diameter) decreased. The nerve fibers in both muscles were less visible and discontinuous. In the soleus muscle the predominant type I fibers decreased and type II increased, while in the gastrocnemius were maintained the proportion of the two types of fibers. In both muscles there was positive staining for apoptosis and/or nuclear autophagocytosis which was more pronounced in the soleus. In conclusion, immobilization in a plaster bandage causes muscle atrophy already evident at 15 days. The gastrocnemius muscle has lost weight and dimensions, being more affected than the soleus. The connective tissue increases more in the soleus muscle than in gastrocnemius as well as the labeling to apoptosis and/or nuclear autophagocytosis. The soleus shows a predominance of type I fibers to 30 days and the gastrocnemius has similarities to both types of muscle fibers in all times of immobilization. Already nervous tissue behaved equally in both muscles, with less visible and discontinued after 45 days. The soleus muscle is less sensitive to the immobilization that gastrocnemius detention to 45 days, but more vulnerable to atrophy due to having more type I fibers and has a higher chance of apoptosis and/or nuclear autophagocytosis, confirmed by a stronger staining for caspase 3.